Answer :





6(x2 + 1) = 13x


6x2 + 6 = 13x


6x2 – 13x + 6 = 0


6x2 – 9x – 4x + 6 = 0


taking 3x common from first two terms and – 2 common from next two


3x(2x – 3) – 2(2x – 3) = 0


(3x – 2)(2x – 3) = 0


3x – 2 = 0 or 2x – 3 = 0


3x = 2 or 2x = 3


Therefore and


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Introduction to Linear Equations in Two VariablesIntroduction to Linear Equations in Two VariablesIntroduction to Linear Equations in Two Variables62 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve the followiGujarat Board Mathematics

Solve the followiGujarat Board Mathematics

Solve the followiGujarat Board Mathematics

Solve the followiGujarat Board Mathematics

Solve the followiGujarat Board Mathematics

Solve the followiGujarat Board Mathematics

Solve the followiGujarat Board Mathematics

Solve the followiGujarat Board Mathematics

Solve the followiGujarat Board Mathematics

Solve the followiGujarat Board Mathematics